2020
DOI: 10.15252/embr.202051929
|View full text |Cite
|
Sign up to set email alerts
|

IRE1‐mediated miRNA maturation in macrophage phosphoinositide signaling

Abstract: Endoplasmic reticulum (ER) stress signaling has long been associated with various pathological states in particular with the development of diseases with an underlying inflammation, such as diabetes, liver or cardiovascular dysfunctions, and cancer. ER stress signaling is mediated by three stress sensors. The most evolutionarily conserved one, the inositol‐requiring enzyme 1 alpha (IRE1), transduces most of the signals through an endoribonuclease (RNase) activity toward RNAs including mRNAs and microRNAs (miRN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…However, further research is necessary to clarify the role of IRE1α and its relationship to enhanced drug efflux in HCC. One important aspect of IRE1α’s endoribonuclease activity is that this is not only responsible for cleaving XBP1, but several studies have shown that IRE1α is also able to cleave and regulate miRNAs [ 45 , 46 , 47 ]. ER stress has therefore been shown to contribute to the miRNA imbalance in inflammation [ 47 ] and cancer [ 48 ].…”
Section: Mechanisms Of Drug Resistancementioning
confidence: 99%
“…However, further research is necessary to clarify the role of IRE1α and its relationship to enhanced drug efflux in HCC. One important aspect of IRE1α’s endoribonuclease activity is that this is not only responsible for cleaving XBP1, but several studies have shown that IRE1α is also able to cleave and regulate miRNAs [ 45 , 46 , 47 ]. ER stress has therefore been shown to contribute to the miRNA imbalance in inflammation [ 47 ] and cancer [ 48 ].…”
Section: Mechanisms Of Drug Resistancementioning
confidence: 99%
“…Nevertheless, several studies have identified RIDD-degraded mRNAs that encode cytosolic or nuclear proteins (including XBP1 ), illustrating that the IRE1 substrates do not necessarily require an ER a signal sequence (Kraut-Cohen and Gerst 2010 ; Pyhtila et al 2008 ; Lerner et al 2003 ; Diehn et al 2000 ). Importantly, IRE1 has also been shown to degrade several pre-miRNAs (Upton et al 2012 ; Gebert et al 2023 ) and to facilitate maturation of miRNA precursors in a DICER-independent manner (Avril and Chevet 2020 ). Because IRE1 is also localized in the inner nuclear envelope (Schroder and Kaufman 2005 ), these precursors could be processed as they encounter IRE1 while traversing the nuclear pore on their way to the cytoplasm (Upton et al 2012 ).…”
Section: The Role Of Ire1 In Cell Fate Decisionsmentioning
confidence: 99%
“…Several works already demonstrated the involvement of IRE1 in miRNA regulation. Indeed, IRE1 regulates the expression of miR-316 and miR-148a by regulating the transcription of miRNA-related transcription factors [ 73 ]. The work from Hamid and colleagues demonstrates that IRE1 can directly control the maturation of an miRNA in a Dicer-independent fashion [ 72 ].…”
Section: Small Ncrnasmentioning
confidence: 99%
“…IRE1 is a known ER-stress sensor and promoter of adaptive stress responses caused by the accumulation of unfolded proteins in the ER. IRE1 activity can be enhanced also by the incorporation of saturated fatty acids (SFA) or free cholesterol within the ER [ 72 , 73 ]. Indeed, although the ER plays a central role in lipid metabolism, it is poor in cholesterol and SFA.…”
Section: Non-canonical Function Of Ncrnas In Cvdmentioning
confidence: 99%